Formação de professores para o trabalho com o tema sexualidade no cotidiano escolar - Oliveira, Rosemary Rodrigues de [UNESP]; Brancaleoni, Ana Paula Leivar [UNESP]; Souza, Tatiana Noronha de [UNESP] (My University, 2013)
The current study aims to examine the training potential of an extension project, to work with the issue of sexuality in the daily school environment, as well as the redefinition of values and prejudices on the part of students. Sexuality relates to the pursuit of pleasure, manifested from birth to death. It is believed that the school environment is permeated with sexuality and the school can not deny its role in informing and training young people to experience it sensibly and safe. The extension project in question is intended to constitute as training space for Biological Sciences undergraduates at a public university, to provide conditions for reflection and subjectification of issues related to sexuality, favoring the training of more qualified teachers to deal with the subject in school environment. We used a qualitative methodology, using as instruments to collect data: questionnaires consisting of open-ended questions answered by members and former members of the design and analysis of mentoring records of supervision. It appears that participation in the project is perceived as significant and indicated as responsible for changes in conceptions, prejudices, stereotypes and attitudes regarding the theme of sexuality. Participants feel better prepared to work with the theme in their teaching practice.

O presente estudo tem por objetivo analisar o potencial formativo de um projeto de extensão, para atuação com a questão da sexualidade no cotidiano escolar, assim como a re-significação de valores e preconceitos por parte de universitários. A sexualidade relaciona-se à busca do prazer, manifestada do nascimento à morte. Acredita-se que o ambiente escolar é permeado pela sexualidade e não pode negar o seu papel na informação e formação dos jovens para que a vivenciem de forma refletida e segura. O Projeto de Extensão em questão visa se constituir enquanto espaço formativo para os licenciandos Ciências Biológicas de uma Universidade Pública, a fim de proporcionar condições de reflexão e subjetivação de questões referentes à sexualidade, favorecendo a formação de professores mais capacitados para lidar com o tema no cotidiano escolar. Utilizou-se uma metodologia qualitativa, tendo como instrumentos de coleta de dados: questionários, compostos por questões abertas, respondidos por integrantes e ex-integrantes do Projeto e análise dos registros de supervisão. Constata-se que a participação no projeto é percebida como significativa, sendo indicada como responsável por mudanças de concepções, preconceitos, estereótipos e posturas referentes ao tema sexualidade. Entendem-se ainda mais preparados para o trabalho com o tema em sua atuação docente.
Teacher education for working with the theme sexuality in school everyday
Keywords: Teacher training; Sexuality; University extension; Formação de professores; Sexualidade; Extensão universitária